G-Jitter free convection flow in the stagnation-point region of a three-dimensional body - Shafie, Sharidan; Amin, Norsarahaida; Pop, Ioan (Pergamon Press, 2007)
A numerical solution of the effect of a small fluctuating gravitational field characteristic of g-jitter is presented. Specifically the problem of free convection boundary layer flow near a three-dimensional stagnation point of attachment resulting from a step change in its constant surface temperature is considered. The transformed non-similar boundary layer equations are solved using the Keller-box method, which is essentially an implicit finite-difference scheme. Numerical results are given for a value of the Prandtl number, Pr = 0.72 with the forcing amplitude, Îµ, and the forcing frequency, Î©. It is shown that g-jitter affects considerably the flow characteristics, namely the skin friction and the rate of heat transfer. Comparison with earlier results for the case of constant gravity field show very good agreement.